The GCTM‐5 Epitope Associated with the Mucin‐Like Glycoprotein FCGBP Marks Progenitor Cells in Tissues of Endodermal Origin123. (20th August 2012) - Stamp, Lincon A.; Braxton, David R.; Wu, Jun; Akopian, Veronika; Hasegawa, Kouichi; Chandrasoma, Parakrama T.; Hawes, Susan M.; McLean, Catriona; Petrovic, Lydia M.; Wang, Kasper; Pera, Martin F.
Abstract: Monoclonal antibodies against cell surface markers are powerful tools in the study of tissue regeneration, repair, and neoplasia, but there is a paucity of specific reagents to identify stem and progenitor cells in tissues of endodermal origin. The epitope defined by the GCTM‐5 monoclonal antibody is a putative marker of hepatic progenitors. We sought to analyze further the distribution of the GCTM‐5 antigen in normal tissues and disease states and to characterize the antigen biochemically. The GCTM‐5 epitope was specifically expressed on tissues derived from the definitive endoderm, in particular the fetal gut, liver, and pancreas. Antibody reactivity was detected in subpopulations of normal adult biliary and pancreatic duct cells, and GCTM‐5‐positive cells isolated from the nonparenchymal fraction of adult liver expressed markers of progenitor cells. The GCTM‐5‐positive cell populations in liver and pancreas expanded greatly in numbers in disease states such as biliary atresia, cirrhosis, and pancreatitis. Neoplasms arising in these tissues also expressed the GCTM‐5 antigen, with pancreatic adenocarcinoma in particular showing strong and consistent reactivity. The GCTM‐5 epitope was also strongly displayed on cells undergoing intestinal metaplasia in Barrett's esophagus, a precursor to esophageal carcinoma. Biochemical, mass spectrometry, and immunochemical studies revealed that the GCTM‐5 epitope is associated with the mucin‐like glycoprotein FCGBP. The GCTM‐5 epitope on the mucin‐like glycoprotein FCGBP is a cell surface marker for the study of normal differentiation lineages, regeneration, and disease progression in tissues of endodermal origin. Stem Cells 2012;30:1999–2009